THE RELATIONSHIP BETWEEN THE INCIDENT OF DYSMENORRHEA AND THE PERFORMANCE OF NURSES AT BHAYANGKARA HOSPITAL BRIMOB KELAPADUA DEPOK IN 2023 - Mastiti, Kurniati Puji; Yuliani, Indah (HEARTY, 2025)
Background: Based on an initial survey conducted by researchers at the Bhayangkara Brimob Kelapadua Hospital, Depok, data was obtained that out of 122 female nurses, 70 (57%) nurses experienced dysmenorrhea which could interfere with performance because it caused the services provided to be less than optimal. Purpose: To determine the relationship between the incidence of dysmenorrhea and the performance of nurses at the Bhayangkara Brimob Kelapadua Hospital, Depok in 2023. Methods: Cross sectional through a point time approach where samples were taken using a total sampling of 70 respondents. Data analysis using chi square test. Results: There is no significant relationship between the incidence of dysmenorrhea and nurse performance, this is shown by the value (p-value 0,183). Conclusion: There is no significant relationship between the incidence of dysmenorrhea and the performance of nurses at the Bhayangkara Brimob Kelapadua Hospital, Depok, so that nurses can still provide optimal nursing care services even though they are experiencing dysmenorrhea.